Atmospheric Electrical Activity in central Argentina and its relationship with phenomena observed at the Auger Observatory. Issue 1 (1st December 2022) - Nicora, M G; Baissac, D M; Villagran, C I; Velazquez, Y; Solari, F I; Barle, M F; Pini, L; Bertone, F
Abstract: Thunderstorms in Argentina have great spatial variability explained by various mechanisms on different spatio-temporal scales, associated with the meridional extension and orography of the region. The Pierre Auger Observatory is located in Mendoza Province in central-western Argentina where the unique meteorological and geographical conditions result in a high spacial density of convective storms. Atmospheric electrical activity (AEA) produces Transient Luminous Events (TLEs) of which ELVES are the most prominent members of the extraordinary family that includes halos, jetstorms, and sprites. Northern Argentina and Southern Brazil are prolific producers of TLEs, which can be observed at the Pierre Auger Observatory by the Fluorescence Detector (FD) 24 UV telescope. In this work, we present the characterization of the AEA in the study region and the most important meteorological characteristics to aid in understanding which of the dynamical or microphysical processes could act in the formation of TLEs.